Psychological Factors of Formation of the European Christian Culture in Terms of the Theory of Sense Transformations - Zhovtianska, Valeria (Psychological Prospects Journal, 2020)
The article presents an attempt to determine the psychological factors of historical process on the example of the formation of European Christian culture. The detecting of these factors was carried out on the basis of the theory of sense transformations, which describes the psychological mechanisms of the development of subjective representations of reality. From the point of view of this theory, there are rational and irrational subjective representations that are different in the way they function. For the first of them a propositional form of expression is relevant and they require the use of reflection and verification. For the second of them the figurative form of expression is relevant and they do not need verification. The article describes features of European Christian culture as a consequence of the development of subjective representations dominated in the society of that time. The initial prerequisite for the formation of European Christian culture is seen in the collapse of ancient myth, which in turn was the result of the use of reflection in the formation of subjective representations. A significant part of its functions is taken over by the Christian religion, which becomes a worldview dominant for young European culture. The reason for this was the relatively low level of the culture of thinking and, above all, reflexivity among the peoples who conquered the ancient world and adopted Christianity from it. The same low level of reflexivity, as well as the irrelevance of propositional forms of expression for irrational representations became prerequisites for meaningful transformations of the original Christian teaching. Transformed religious representations, which occupied a dominant place in the medieval worldview, determined specific features of the culture of the Middle Ages and left their mark on the entire lifestyle of society at that time.